Sex‐Based Disparities in Incidence, Treatment, and Outcomes of Cardiac Arrest in the United States, 2003–2012. Issue 6 (22nd June 2016) - Kim, Luke K.; Looser, Patrick; Swaminathan, Rajesh V.; Horowitz, James; Friedman, Oren; Shin, Ji Hae; Minutello, Robert M.; Bergman, Geoffrey; Singh, Harsimran; Wong, S. Chiu; Feldman, Dmitriy N.
Abstract : Background: Recent studies have shown improving survival after cardiac arrest. However, data regarding sex‐based disparities in treatment and outcomes after cardiac arrest are limited. Methods and Results: We performed a retrospective analysis of all patients suffering cardiac arrest between 2003 and 2012 using the Nationwide Inpatient Sample database. Annual rates of cardiac arrest, rates of utilization of coronary angiography/percutaneous coronary interventions/targeted temperature management, and sex‐based outcomes after cardiac arrest were examined. Among a total of 1 436 052 discharge records analyzed for cardiac arrest patients, 45.4% (n=651 745) were females. Women were less likely to present with ventricular tachycardia/ventricular fibrillation arrests compared with men throughout the study period. The annual rates of cardiac arrests have increased from 2003 to 2012 by 14.0% ( P trend <0.001) and ventricular tachycardia/ventricular fibrillation arrests have increased by 25.9% ( P trend <0.001). Women were less likely to undergo coronary angiography, percutaneous coronary interventions, or targeted temperature management in both ventricular tachycardia/ventricular fibrillation and pulseless electrical activity/asystole arrests. Over a 10‐year study period, there was a significant decrease in in‐hospital mortality in women (from 69.1% to 60.9%, P trend <0.001) and men (from 67.2% to 58.6%, P trend <0.001) after cardiac arrest. In‐hospital mortality was significantly higher in women compared with men (64.0% versus 61.4%; adjusted odds ratio 1.02, P <0.001), particularly in the ventricular tachycardia/ventricular fibrillation arrest cohort (49.4% versus 45.6%; adjusted odds ratio 1.11, P <0.001). Conclusions: Women presenting with cardiac arrests are less likely to undergo therapeutic procedures, including coronary angiography, percutaneous coronary interventions, and targeted temperature management. Despite trends in improving survival after cardiac arrest over 10 years, women continue to have higher in‐hospital mortality when compared with men.